ANALISA BEBAN PENGEREMAN TERHADAP KUALITAS KAMPAS REM TROMOL MOBIL DENGAN METODE OGHOSI - Taufiq, M. Qurohman; ., Syarifudin (MATEMATIKA, 2016)
The development of technology is currently grows rapidly now and the impact from the development is there will be a wide variety of design technology, especially in the field of automotive engine and methods. Therefore it needs a lot of research and analysis, one of them is the braking load for the braking pressure, wearing and the resulting of quality. The purpose of this study was to determine the thickness of the wearing of the brake drum testing and to know the quality of the brake drum car. The method in this research by collecting data with the literature, observation and experimentation, and used analytical Oghosi method. The type of vehicle in this study is Diesel Isuzu Panther. To get a good quality of brake linings, the material must have these characteristics such as : a high coefficient of friction, the material characteristic is not influenced by the environment and condition, the resistance to high temperatures and the resistance to wearing and friction. In the research braking loads is started from 5 kg to 25 kg which is obtained values ​​ranging from 0,00381 mm2/Kg up to 0,00809 mm2/Kg. Therefore, in this study concluded that the addition of loads was greater than the addition of a specific value shrinking, it is influenced by the presence of a higher traction due to greater loading.